Improving the timeliness of resolving client queries in XYZ Company - Arboleda, Jian Carla Banayad (Animo Repository, 2022)
This action research addressed the delay in resolving client cases handled by the Ownership Team. The timeliness issue was identified through brainstorming with collaborators and analysis of the quantitative data of our performance in the Content to Client (C2C) process. One of the manifestations of the issue was the unresponsiveness of Content Analysts or our market experts in acknowledging client query emails. The inquiry tools used in the first cycle led us to focus on solving the knowledge gap of the C2C process within the team. My collaborators and I were guided by the Knowledge Management Process Model, GRPI Model, and ADKAR Model for change management. After implementing the Content to Client (C2C) E-handbook, we failed to meet all the KPIs for Cycle 1. Such resulted in shifting our concentration to specific cases in the next cycle. In Cycle 2, together with my collaborators, we delved into the timeliness of the Manila Ownership team’s Data Corrected Cases (DCC). Consistent with our main goal, which is to expedite the investigation and resolution of client cases by equipping everyone with the proper knowledge, we provided additional information in the C2C reference documents and improved the communication process among the team. As a result, we obtained positive resolution timeliness scores in the Market Driven Metrics (MDM) for August 2022. During the course of the action research, I realized the need to revisit Ownership’s knowledge management initiatives. After careful reflection, I thought of continuing to improve this area even after my action research project.